Exploring Hebephrenic Schizophrenia Through the Lens of Skinnerian Behaviorism with Consideration of Substance Abuse History - Pawasa, Cholifia Sarining; Satiningsih, Satiningsih (Proceedings of The International Conference on Psychology and Education, 2024)
This study explores hebephrenic schizophrenia in a 21-year-old man, initials MY, with a history of drug abuse. Using qualitative methods and a case study approach, this research was conducted at RSJ X, East Java, for two weeks. Data were collected through documentation study, observation, and interviews, involving the subject and his family. Data analysis followed the Miles and Huberman technique, including data reduction, data presentation, and conclusion drawing. The results showed that the subject experienced symptoms of hebephrenic schizophrenia, including disorganized behavior, affective disorders, and fragmentary hallucinations. A history of drug abuse, family conflict, and pressure from the work environment are factors that worsen the subject’s mental condition. The death of the grandfather who was very close to the subject also played a significant role in triggering the disorder. This study emphasizes the importance of holistic interventions in the treatment of hebephrenic schizophrenia, especially those involving psychosocial factors and substance use.